2019
DOI: 10.1186/s12889-019-7068-7
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and remaining teeth in Japan: results from the Toyama dementia survey

Abstract: Background The prevalence of periodontal disease is increasing among elderly individuals in Japan. Reports on the risk factors for tooth loss have included socioeconomic status (SES); however, few studies have addressed the association between remaining teeth and SES by examining whether education and occupation have a synergistic effect on tooth loss. Accordingly, the present study evaluated the association of remaining teeth with the socioeconomic factors of educational and occupational historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
(23 reference statements)
4
17
1
Order By: Relevance
“…Our findings on the link between social inequalities and tooth loss are consistent with previous population-based single-level studies conducted in the Uruguay, Korea and Japan despite the methodological differences in the sample size, sample age group, sampling procedures, definition of outcome (e.g., severe tooth loss, number of remaining teeth) and measures of socioeconomic status (e.g., occupational history, income) [6][7][8]. Overall, these studies showed a high prevalence of tooth loss in the studied samples.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings on the link between social inequalities and tooth loss are consistent with previous population-based single-level studies conducted in the Uruguay, Korea and Japan despite the methodological differences in the sample size, sample age group, sampling procedures, definition of outcome (e.g., severe tooth loss, number of remaining teeth) and measures of socioeconomic status (e.g., occupational history, income) [6][7][8]. Overall, these studies showed a high prevalence of tooth loss in the studied samples.…”
Section: Discussionsupporting
confidence: 90%
“…Secondary analysis of nationwide oral health surveys in different countries reported the influence of poor individual socioeconomic characteristics, such as family income, occupational history and educational level, on tooth loss among elders and adults [5][6][7][8]. These findings are in accordance with a recent systematic that concluded that lower levels of education and poor income were meaningful factors associated with edentulism among elderly people [9].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study, a total of 294 studies were considered for further review, including the results of key words search (n=290) and additional records identi ed from relevant reviews and reference lists of other studies (n=4). Through the careful reading of full texts, seven cohort studies [12][13][14][15][16][17][18] and nine cross-sectional studies [19][20][21][22][23][24][25][26][27] were thought eligible for meta-analysis ( Figure 1).…”
Section: Literature Selectionmentioning
confidence: 99%
“…Six included studies [12][13][14][15][16]19] reported the association between tooth loss and incident hypertension, among which one study [15] reported incidence of diabetes among participants with edentulism. The other nine studies reported the association between hypertension and incidence of tooth loss, among which four studies [24][25][26][27] were concerned on the incidence of edentulism. The main information of eligible studies was given in Table 1.…”
Section: Literature Selectionmentioning
confidence: 99%